Pengaruh Penggunan Flashcard dalam Meningkatkan Pengetahuan tentang Pengenalan Gigi dan Fungsinya pada Siswa/i TK - Munawaroh, Sinta Fajar; Chaerudin, Denden Ridwan; Ningrum, Nining; Heryanto, Yonan (Poltekkes Kemenkes Bandung, 2025)
Learning activities at Nurul Inayah Kindergarten, Garut, still encounter difficulties in choosing learning media that align with the developmental characteristics of early childhood. Many children have limited understanding of teeth and their functions because they have not received targeted education or counseling about this topic. This study aimed to analyze the influence of flashcard use on improving students’ knowledge of teeth and their functions. The research employed a quantitative analytical approach with a pre-experimental one-group pretest–posttest design. The research was conducted in March - October 2025. A total of thirty students from Nurul Inayah Kindergarten, Garut, took part in three learning sessions using flashcards, and their knowledge was assessed using a 12-item questionnaire. Prior to the intervention, all participants (100%) were categorized as having low knowledge levels. After the implementation of flashcards, the percentage of students in the high knowledge category increased to 100% in group 1, 70% in group 2, and 60% in group 3. The Wilcoxon Signed Rank Test revealed a p-value of 0.000 (<0.05), confirming a significant improvement in students’ understanding. In summary, the use of flashcards proved effective in enhancing knowledge about teeth and their functions among students at Nurul Inayah Kindergarten, Garut.